Implementasi Media Piramida Makanan Dalam Pembelajaran Jaring-Jaring Makanan untuk Mengeksplorasi Respon Siswa Kelas V SDN Bandung 1 Jombang - Ilma Hidayah; Evi Rizqi Salamah (IJPSE Indonesian Journal of Primary Science Education, 2026)
This study aims to describe the implementation of food pyramid media in teaching food webs and to explore the responses of fifth-grade students at SDN Bandung 1 Jombang. The study was motivated by learning activities that were still centered on teacher explanations without the support of instructional media. As a result, the abstract concept of food webs was not optimally understood, causing students to be passive and experience difficulties in connecting the material to their daily lives. This condition indicates the importance of using concrete and visual learning media to help students understand food web concepts while exploring their responses during the learning process. This research employed a qualitative approach with a descriptive design. The research subjects were fifth-grade students. Data were collected through observation, interviews, and documentation. Data analysis was conducted through data reduction, data display, and inductive conclusion drawing. The results showed that the implementation of food pyramid media was able to concretize food web concepts, making learning more interactive and meaningful. Students’ responses were identified in the cognitive, affective, and psychomotor domains. The obstacles encountered included limited time, differences in students’ abilities, and limitations in media size. Therefore, the implementation of concrete media should be accompanied by effective classroom management and appropriate guidance to ensure equal learning experiences. Thus, food pyramid media can serve as an innovative alternative to improve science learning quality in elementary schools.